2021
DOI: 10.1186/s10194-021-01260-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of onabotulinumtoxinA reduces healthcare resource utilization in individuals with chronic migraine: the REPOSE study

Abstract: Background Chronic migraine (CM) is associated with substantial economic burden. Real-world data suggests that onabotulinumtoxinA treatment for CM reduces healthcare resource utilisation (HRU) and related costs. Methods REPOSE was a 2-year prospective, multicentre, non-interventional, observational study to describe the real-world use of onabotulinumtoxinA in adult patients with CM. This analysis examined the impact of onabotulinumtoxinA on HRU. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
4
15
0
1
Order By: Relevance
“…11,12 Furthermore, BoNTA demonstrated its efficacy in about 70% of treated patients after three courses of BoNTA on all clinical and quality of life measures and a favorable benefit-risk ratio in subsequent PREEMPT pooled subgroup analysis of CM patients with or without MOH. [13][14][15] Real-world data have also been consistent with the positive benefit-risk profile of BoNTA ascertained in all PREEMPT-based publications, in addition to demonstrating improvements on patientreported outcomes (PROs), 16 even in the context of direct head-tohead comparison with topiramate. 17 Finally, real-world long-term experience with BoNTA in CM patients for up to four years of treatment supports its sustained efficacy and adequate safety and tolerability over time.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…11,12 Furthermore, BoNTA demonstrated its efficacy in about 70% of treated patients after three courses of BoNTA on all clinical and quality of life measures and a favorable benefit-risk ratio in subsequent PREEMPT pooled subgroup analysis of CM patients with or without MOH. [13][14][15] Real-world data have also been consistent with the positive benefit-risk profile of BoNTA ascertained in all PREEMPT-based publications, in addition to demonstrating improvements on patientreported outcomes (PROs), 16 even in the context of direct head-tohead comparison with topiramate. 17 Finally, real-world long-term experience with BoNTA in CM patients for up to four years of treatment supports its sustained efficacy and adequate safety and tolerability over time.…”
Section: Introductionsupporting
confidence: 67%
“…In addition, there is evidence to support the beneficial effect of BoNTA injections at different sites, not just the forehead, in reducing the frequency and severity of comorbid psychiatric disorders, including depression and anxiety 47,48 . Finally, the real‐life efficacy/safety evidence that has been collected on BoNTA since the date it was first marketed for the treatment of CM is significantly richer, compared with MAbs against CGRP or CGRP receptor 16,49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Canadian population based study, 77% of migraineurs reported restriction in their functional ability, 50% had to discontinue the normal activities, 30% had to cancel family or social activities, and 19% reported missing work time during their last migraine attack [ 38 ]. OnabotulinumtoxinA is a cost-effective treatment for chronic migraine and is associated with decreased healthcare utilization [ 39 , 40 ]. Severe headache days have more impact on the function and productivity of patients and hence impose higher financial burden on the patients and employers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a reduction in percentage of 77% and 78% of patients absent from school or work as well as an increased performance at school or work over the 2-year period. Therefore, no patients reported headacherelated disability at visit 8 [96].…”
Section: Impact Of Botulinum Toxin Treatment In Migraine On Social Bu...mentioning
confidence: 95%